Sensitivity of different taxonomic levels of soil Gamasina to land use and anthropogenic disturbances - Bedano, José Camilo (2010)
The effect of taxonomic level on the sensitivity of bioindicators has been widely investigated in aquatic ecosystems and, to a lesser extent, in terrestrial ecosystems. However, no studies have been conducted on the sensitivity of the different taxonomic levels of soil mites, especially Gamasina, to human activities. The present study aimed to assess the sensitivity of different taxonomic levels of soil Gamasina mites to anthropogenic disturbances in Europe and Argentina. We arranged the data from previous projects in a hierarchical system and conducted a study to identify the critical taxonomical levels that had the highest discriminative potential between sites (Europe and Argentina) or management types (forests, grasslands, fallows, succession, recultivation and agricultural sites). For the Gamasina community, geographical location was by far more important than the influence of any land use type. The analysis including only the European sites demonstrated that communities belonging to sites subjected to different land uses were also significantly different. The species data set provided a clearer separation of sites according to both the geographical and the land-use gradients than the genus and family data sets. The genus and, to a lesser extent, the family approach may be sufficient to elucidate the influence of great geographical differences and also of certain land uses (e.g. grasslands from the forests and arable sites).5 Species presence/absence data provided valuable information in our analyses, although the use of quantitative data yielded a clearer separation of sites.